Tailoring graphene-based electrodes from semiconducting to metallic to increase the energy density in supercapacitors. (29th October 2015) - Vatamanu, Jenel; Ni, Xiaojuan; Liu, Feng; Bedrov, Dmitry
Abstract: The semiconducting character of graphene and some carbon-based electrodes can lead to noticeably lower total capacitances and stored energy densities in electric double layer (EDL) capacitors. This paper discusses the chemical and electronic structure modifications that enhance the available energy bands, density of states and quantum capacitance of graphene substrates near the Fermi level, therefore restoring the conducting character of these materials. The doping of graphene with p or n dopants, such as boron and nitrogen atoms, or the introduction of vacancy defects that introduce zigzag edges, can significantly increase the quantum capacitance within the potential range of interest for the energy storage applications by either shifting the Dirac point away from the Fermi level or by eliminating the Dirac point. We show that a combination of doping and vacancies at realistic concentrations is sufficient to increase the capacitance of a graphene-based electrode to within 1 μ F cm −2 from that of a metallic surface. Using a combination of ab initio calculations and classical molecular dynamics simulations we estimate how the changes in the quantum capacitance of these electrode materials affect the total capacitance stored by the open structure EDL capacitors containing room temperature ionic liquid electrolytes.